Antibacterial and fungicidal activities of ethanol extracts of 38 species of plants - Zazharskiy, Vladymyr; Zazharskiy, Volodymyr; Zazharskyi, Vladymyr; Zazharskyi, Volodymyr; Zazharskiy, V.; Zazharskyi, V.; Zazharskiy, Volodymyr V.; Zazharskiy, V. V.; Zazharskyi, V. V.; Zazharsky, V. V.; Зажарський, Володимир Володимирович; Davydenko, Pavel; et al. (Oles Honchar Dnipropetrovsk National University, 2020)
Galenic preparations are broadly used against microorganisms pathogenic to humans, thought their poteintial in this aspect is not studied completely. In our in vitro experiment we studied the influence of alcohol tinctures from 38 species of plants on 15 species of bacteria and one species of fungus. Zones of growth inhibition of colonies measuring over 8 mm were observed during the use of ethanol extracts of Maclura pomifera against eight species of microorganisms (Escherichia сoli, Proteus mirabilis, Serratia marcescens, Yersinia enterocolitica, Salmonella typhimurium, Rhodococcus equi, Campylobacter jejuni and Corynebacterium xerosis), Ginkgo biloba – against eight species (Enterococcus faecalis, S. marcescens, Y. enterocolitica, Klebsiella pneumoniae, Listeria іnnocua, L. monocytogenes, Р. аeruginosa and C. jejuni), Genista tinctoria – against seven species (E. coli, Enterobacter aerogenes, Proteus mirabilis, K. pneumoniae, S. typhimurium, Р. аeruginosa and Rh. equi), Phellodendron amurense – against seven species (E. faecalis, S. marcescens, S. typhimurium, Rh. equi, C. jejunі, C. xerosis and Candida albicans), Berberis vulgaris – against seven species (P. mirabilis, S. marcescens, K. pneumoniae, S. typhimurium, C. jejuni, Р. аeruginosa and C. xerosis), Vitex negundo – against six species (E. faecalis, E. coli, P. mirabilis, K. pneumoniae, S. typhimurium and Rh. equi), Koelreuteria paniculata – against six species (E. faecalis, P. mirabilis, S. marcescens, S. typhimurium, C. jejunі and E. coli), Magnolia kobus – against six species (E. faecalis, E. coli, P. mirabilis, S. marcescens, S. typhimurium, C. jejunі and C. xerosis), Liriodendron tulipifera – against six species (K. pneumoniae, Listeria іnnocua, Р. аeruginosa, C. jejuni, Rh. equi and C. albicans), Clematis flammula – against six species (E. faecalis, P. mirabilis, L. monocytogenes, Р. аeruginosa, C. jejuni and C. xerosis), Wisteria sinensis – against five species (E. coli, S. typhimurium, L. monocytogenes, Rh. equi and C. albicans), Chimonanthus praecox – against five species (E. faecalis, S. marcescens, L. monocytogenes, C. jejuni and Rh. equi), Colchicum autumnale – against five species (S. marcescens, K. pneumoniae, L. ivanovi, L. monocytogenes and Р. аeruginosa). As a result of the study, these plants were found to be the most promising for further study of in vivo antibacterial activity. In the search of antibacterial and antifungal activities, the following plants were observed to be less promising: Ailanthus altissima, Aristolochia manshuriensis, Artemisia absinthium, Callicarpa bodinieri, Campsis radicans, Catalpa duclouxii, Celastrus scandens, Dictamnus alba, Eucommia ulmoides, Geranium sanguineum, Laburnum anagyroides, Nepeta racemosa, Parthenocissus tricuspidata, Polygonatum multiflorum, Prunus dulcis, P. laurocerasus, Ptelea trifoliata, Pteridium aquilinum, Quercus castaneifolia, Q. petraea iberica, Salvia officinalis, Securigera varia, Styphnolobium japonicum, Tamarix elongata and Vitex agnus-castus. Галенові препарати широко застосовуються проти патогенних для людини мікроорганізмів, вважаючи, що їх потенціал у цьому аспекті вивчений не повністю. В експерименті in vitro ми вивчали вплив спиртових настоянок з 38 видів рослин на 15 видів бактерій та один вид гриба. Зони пригнічення росту колоній розміром понад 8 мм спостерігались під час використання етанолових екстрактів Maclura pomifera проти восьми видів мікроорганізмів (Escherichia сoli, Proteus mirabilis, Serratia marcescens, Yersinia enterocolitica, Salmonella typhimurium, Rhodococcus equi, Campylobacter jejunium xterium xeniuni ), Гінкго білоба - проти восьми видів (Enterococcus faecalis, S. marcescens, Y. enterocolitica, Klebsiella pneumoniae, Listeria іnnocua, L. monocytogenes, Р. аeruginosa та C. jejuni), Liriodendron tulipifera - проти шести видів (K. pneumoniae, Listeria іnnocua, Р. аeruginosa, C. jejuni, Rh. Equi та C. albicans), Clematis flammula - проти шести видів (E. faecalis, P. mirabilis, L. monocytogenes, Р. аeruginosa, C. jejuni та C. xerosis), Wisteria sinensis - проти п’яти видів (E. coli, S. typhimurium, L. monocytogenes, Rh. Equi та C. albicans), Chimonanthus praecox - проти п’яти видів (E. faecalis, S. marcescens, L. monocytogenes, C. jejuni та Rh. equi), Colchicum autumnale - проти п’яти видів (S. marcescens, K. pneumoniae, L. ivanovi, L. monocytogenes та Р. аeruginosa). В результаті дослідження було виявлено, що ці рослини є найбільш перспективними для подальшого вивчення антибактеріальної активності in vivo.
Антибактеріальна та фунгіцидна активність етанолових екстрактів 38 видів рослин
Зажарський Володимир Володимирович https://orcid.org/0000-0003-2674-2494 Давиденко Павло Олександрович https://orcid.org/0000-0002-8425-3835 Кулішенко Олег Миколайович https://orcid.org/0000-0001-6801-2380 Боровик Ірина Володимирівна https://orcid.org/0000-0001-5958-8396 Зажарська Надія Миколаївна https://orcid.org/0000-0002-8328-6440
Keywords: candidosis; кандидоз; growth inhibition zone; зона гальмування росту; bacterial colonies; колонії бактерій; multi-resistant strain; мультистійкий штам